PREPARATION OF MUKTA BHASMA BY TWO DIFFERENT METHODS AND ITS COMPARATIVE ANALYTICAL STUDY - Prakash Adhav, Ketki; H. Lahare, Kunal (International Journal of Ayurveda and Pharma Research, 2015)
Mukta bhasma (calx of pearl) is a unique Rasashastra preparation contains calcium compounds and widely recommended and traditionally used for G.I tract disorders, anti-pyretic and it strengthens bones. Nowadays, every scholar and practitioner must be aware of pharmaceutical processing of minerals and metals and prevent the toxicity of medicine from the prepared final product. The aim of study is to compare Pharmaceutical and Analysis of Mukta Bhasma prepared by two different methods of Shodhan and Maran and its objective is to carry out Shodhan (purification) and Maran (calcinations) of Mukta (pearls) by two different Methods. The comparison of two samples Mukta Bhasma Godugdha Marit (MBG) & Mukta Bhasma Kulitha Marit (MBK) is carried out by using different analytical methods. The result shows that the Physico-chemical analysis, Solubility, Particle size of both Bhasmas shows similar values. The qualitative analysis for Inorganic Elements like Calcium, Carbonate etc. are present in both Bhasmas. Quantitative analysis of Na, K, Ca by flame photometry found the MBG having 9±1.04, 50±3.76, 283±25.95 and MBK 11±1.04, 53±3.72, 300±23.96 respectively. The Mukta Bhasma prepared with both methods shows similar values and can be suggested that Mukta Bhasma prepared with either method can result in good quantity of Bhasma.